2023
DOI: 10.31083/j.jin2201015
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Improves Some Neurophysiological Parameters but not Clinical Outcomes after Severe Traumatic Brain Injury

Abstract: Background: Disorders of consciousness (DOC) are one of the clinical hallmarks of severe traumatic brain injury (TBI). DOC impair patient life quality and increase the burden on their families and society. Methods: A double-blind, randomized, controlled clinical trial was conducted to determine the efficacy of routine rehabilitation combined with transcranial direct current stimulation (tDCS) in DOC patients after TBI. A total of 78 DOC patients were randomly divided after TBI into two groups: participants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…BK channels are found in microglial cells in various regions of the brain, including the hippocampus, striatum, neocortex, and entorhinal cortex, as well as in the spinal cord following nerve injury (Buttigieg et al, 2011;Regehr and Kaeser, 2014;Schilling and Eder, 2015;Sun et al, 2023). Microglia are immune cells that reside in the brain, and the activity of BK channels regulates their phagocytosis activation and migration (Larson et al, 2016).…”
Section: Bk Channels In Non-neuronal Cells Of the Cnsmentioning
confidence: 99%
“…BK channels are found in microglial cells in various regions of the brain, including the hippocampus, striatum, neocortex, and entorhinal cortex, as well as in the spinal cord following nerve injury (Buttigieg et al, 2011;Regehr and Kaeser, 2014;Schilling and Eder, 2015;Sun et al, 2023). Microglia are immune cells that reside in the brain, and the activity of BK channels regulates their phagocytosis activation and migration (Larson et al, 2016).…”
Section: Bk Channels In Non-neuronal Cells Of the Cnsmentioning
confidence: 99%
“…This study protocol aims to explore the effects and mechanisms of a combined intervention involving HD-tDCS and music for patients with pDOC. Coma Recovery Scale-Revised (CRS-R) ( Fan et al, 2022 ), Glasgow Outcome Scale (GOS) ( Sun et al, 2023 ), and EEG ( He et al, 2018 ) are selected as outcome measures to comprehensively evaluate changes in the consciousness state of patients with pDOC before and after treatment. The findings of this study can provide valuable insights into the development of innovative rehabilitation strategies for this challenging population.…”
Section: Introductionmentioning
confidence: 99%
“…It also enhances neuroplasticity in the brain [ 16 ]. Preliminary research conducted by our research group has demonstrated significant effects of tDCS on patients with TBI [ 17 ], as well as its arousal-promoting effects in comatose rats following TBI. However, the precise therapeutic mechanisms remain not completely comprehended.…”
Section: Introductionmentioning
confidence: 99%